Milk Productivity of Holstein Cows of Different Genotypes - B.S.Abulsaidov; U.T.Rakhimov; S.H.Xushvaqtov; R.A.Mamaraimova; Y.Sh.Abdiqulov (American Journal of Biodiversity, 2024)
With the aim of further improving the economic performance of the planned black-and-white breed, Holstein bulls are widely and effectively used in subsequent years. As a result, Holsteinized offspring with different genotypes were obtained. The article presents data obtained as a result of studying the milk productivity of Holsteinized cattle